Durability of Immunity to SARS-CoV-2 and Other Respiratory Viruses. Issue 7 (July 2021) - Siggins, Matthew K.; Thwaites, Ryan S.; Openshaw, Peter J.M.
Abstract : Even in nonpandemic times, respiratory viruses account for a vast global burden of disease. They remain a major cause of illness and death and they pose a perpetual threat of breaking out into epidemics and pandemics. Many of these respiratory viruses infect repeatedly and appear to induce only narrow transient immunity, but the situation varies from one virus to another. In the absence of effective specific treatments, understanding the role of immunity in protection, disease, and resolution is of paramount importance. These problems have been brought into sharp focus by the coronavirus disease 2019 (COVID-19) pandemic. Here, we summarise what is now known about adaptive immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and draw comparisons with immunity to other respiratory viruses, focusing on the longevity of protective responses. Highlights: Neutralising antibody from long-lived plasma cells, supported by memory B and T cells, can provide lifelong protection against severe disease caused by many respiratory viruses. However, antigenic viral variation can undermine such immunity. Viral immunomodulation of memory responses may contribute to reinfections by certain respiratory viruses, though reinfections of healthy adults with homologous viruses are uncommon and usually mild in severity. Robust systemic antibody, B and T cell responses are mounted upon severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in almost all individuals, and these facets of immune memory are sustained for over 8 months postinfection. Mucosal immunity, provided mainly by IgA and tissue-resident T cells, is associated with rapid and potent protection against respiratory infection. However, the durability of these responses has not been established. Studies of systemic antibody and cellular responses suggest that protection against severe disease caused by nonvariant SARS-CoV-2 may be long-lasting in most individuals.